The effects of excess dietary lysine additions on growth performance and carcass characteristics of finishing pigs - Stoner, G.R.; Goodband, Robert D.; Hines, Robert H.; Nelssen, Jim L.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-five barrows (initial wt 136 lb) were utilized to evaluate the effects of dietary lysine levels ranging from .6 to 1.4% on growth performance and carcass characteristics. Pigs were fed a pelleted corn-sesame meal diet containing .6% lysine (17.7% crude protein) or diets containing .8, 1.0, 1.2, or 1.4% lysine provided by L-Iysine HCl. All other amino acids, vitamins, and minerals were calculated to be at least double the pig's requirement (NRC, 1988), to ensure that no nutrient other than lysine would limit performance. When the pen mean weight reached approximately 235 lb, six pigs per treatment were slaughtered, and carcass data were collected. Increasing dietary lysine level resulted in no differences in average daily gain, feed intake, or feed efficiency. Furthermore, increasing lysine level had no effect on longissimus muscle area, average backfat thickness, loin weight, kidney fat weight, or percentage muscle. However, pigs fed .8% lysine had slightly less backfat and greater percent muscle than pigs fed .6% lysine. These data indicate that dietary lysine additions above .6% do not improve growth performance of finishing barrows; however, increasing the lysine level to .8% may slightly improve carcass leanness.
Keywords: Swine; Lysine; Finishing pigs; Growth performance; Carcass traits